Population dynamics of Farfantepenaeus subtilis (Pérez-Farfante, 1967) and Litopenaeus schmitti (Burkenroad, 1936) (Decapoda: Penaeidae) and evidence of habitat partitioning in the northeast of Brazil - de Carvalho Santos, Rafael [UNESP]; Perroca, Júlia Fernandes [UNESP]; Costa, Rogério Caetano [UNESP]; Hirose, Gustavo Luis (Elsevier, 2020)
The population structure, sex ratio, size at the onset of sexual maturity, growth rates, and longevity of Farfantepenaeus subtilis and Litopenaeus schmitti were studied in the State of Sergipe, Brazil. The distribution pattern of juveniles and reproductive females was compared to investigate whether habitat partitioning takes place between these species. The sampling occurred monthly, from September/2013 to August/2014, in nine stations of three transects (5 m, 15 m, and 30 m deep) using a shrimp fishing boat. In total, 1076 F. subtilis and 499 L. schmitti individuals were captured. The sex ratio of F. subtilis was skewed toward females, while L. schmitti had a 1:1 sex ratio. Females of both species were larger than the males. The size at the onset of sexual maturity of F. subtilis females was large than that of males, while the opposite occurred in L. schmitti. The estimated growth parameters of F. subtilis males were: CL∞=33.24 mm, k = 2.30/year and longevity = 2.0 years. For the females, they were: CL∞=42.49 mm, k = 2.15/year and longevity = 2.12 years. The growth parameters of L. schmitti males were: CL∞=32.48 mm, k = 2.41/year and longevity = 1.91 years. For the females, they were: CL∞=38.78 mm, k = 2.01/year and longevity = 2.29 years. The distribution patterns of juveniles and reproductive females differed between species. F. subtilis females predominated in deeper waters. Juveniles of L. schmitti were aggregated in shallow waters (5 m), while F. subtilis aggregated at 15 m. Considering that (1) the relationship between the environmental factors and the abundance of juveniles and females was not evident, and (2) the reproductive and recruitment periods of these species are synchronized, our results suggest that habitat partitioning takes place to decrease the interspecific competition.
Keywords: Longevity; Maturity; Penaeoidea; Sex ratio; Spatial distribution; von Bertalanffy